A descriptive study of smoking, socioeconomic position, and health-related behaviors in urban Colombia - Valentina Guatibonza-García; Sofía Gnecco-González; Agustín Pérez-Londoño; Carolina Betancourt-Villamizar; Carlos O. Mendivil (Discover Public Health)
Abstract Introduction Data about recent trends in smoking in Latin America are scarce. We estimated the prevalence of smoking, and explored its association with socioeconomic position, health-related behaviors, perceptions, and trusted information sources in Colombian cities. Methods We collected a population-based, multi-stage, stratified probabilistic sample of individuals aged 14–80 years, between November and December 2022. We compared the prevalence of health-related behaviors and perceptions in smokers versus non-smokers employing sample weights according to the sampling design. Results The study included 1904 participants (53.9% female, age 47 ± 19 years). The estimated prevalence of smoking was 22.0% (29.0% in males, 15.7% in females), underage smoking was 4.8%. Among males, the prevalence of smoking was highest in the lowest socioeconomic stratum (31.0%), while among females it was lowest in this stratum (8.3%). Educational level was negatively associated with smoking among men, going from 38.8% for those with only elementary school to 25.5% for college graduates, while among women the trend was the complete opposite. Perceptions about healthy foods and lifestyle habits incorporated in the last year were largely similar between smokers and non-smokers. Smokers and non-smokers appealed essentially to the same health information sources, especially healthcare professionals. Conclusion The worldwide trend towards a reduction in smoking seems to have been reversed in Colombia, smoking is increasing fast in disadvantaged population segments. Strong tobacco control policies should focus on men with less income and lower education. The same communication avenues can be used to convey health information and motivational campaigns to smokers and non-smokers.